1996
DOI: 10.1002/(sici)1097-4644(19960601)61:3<420::aid-jcb9>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol myristate acetate transactivates the avian β3 integrin gene and induces αvβ3 integrin expression

Abstract: 1,25-Dihydroxyvitamin D3 (1,25(OH)2D3)transactivates the avian beta 3 integrin gene whose promoter contains at least two vitamin D response elements, one of which is in close proximity to a candidate AP1 site (TGACTCA). Since fos/jun and steroid hormones interact to regulate gene expression, we asked whether phorbol-12-myristate-13-acetate (PMA), which stimulates binding of fos/jun to AP1 sites, transactivates the avian beta 3 integrin gene and, if so, does the phorbol ester modulate 1,25(OH)2D3 induction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Previous report demonstrated that TPA may upregulate alpha v beta 3 integrin expression in an AP-1 dependent manner [160]. Also, transforming growth factor-beta may up-regulates integrin subunit expression via Smad and Ets signaling [161,162].…”
Section: Expression Of Genes Regulated By Ros For In Emt and Migrationmentioning
confidence: 97%
“…Previous report demonstrated that TPA may upregulate alpha v beta 3 integrin expression in an AP-1 dependent manner [160]. Also, transforming growth factor-beta may up-regulates integrin subunit expression via Smad and Ets signaling [161,162].…”
Section: Expression Of Genes Regulated By Ros For In Emt and Migrationmentioning
confidence: 97%
“…Expression of the α v β 3 integrin is regulated by expression of the β 3 subunit during osteoclast differentiation (Kitazawa et al, 1995;Li et al, 1995;Zhu et al, 1996). We have previously shown that IL-4-dependent expression of the α v β 3 integrin, in osteoclast precursors is mediated by expression of the β 3 gene (Kitazawa et al, 1995) and, using β 3 gene promoter-reporter constructs, we have demonstrated that IL-4 dependent upregulation is directly mediated by the transcription factor STAT-6 (McHugh et al, 2001).…”
Section: Introductionmentioning
confidence: 99%